Effects of Anthracnose on the Structure and Diversity of Endophytic Microbial Communities in Postharvest Avocado Fruits - Xi Chen; Zhuoen Jiang; Peng He; Xiuhua Tang; Haiyun Song; Tao Zhang; Zhejun Wei; Tao Dong; Shufang Zheng; Xinghao Tu; Jian Qin; Jingjing Chen; et al. (Agronomy)
This study aimed to provide foundational research for the biological control of postharvest avocado fruits anthracnose and establish a microbial system of postharvest avocado fruits. The high-throughput sequencing of avocado fruits from the anthracnose-infected and healthy groups was performed using Illumina NovaSeq second-generation sequencing technology. The results revealed that, except for Colletotrichum sp. strain 38#, there were differences in the bacterial community structure of avocados before and after infection, as determined through alpha and beta diversity analysis. Additionally, there were significant differences in the endophytic fungal community structure, allowing clear differentiation between the infected and healthy avocados. The endophytic bacterial community was primarily composed of 4 phyla and 10 genera, with the Bacteroidota phylum and Chryseobacterium genus demonstrating sensitivity to anthracnose pathogens, as evidenced by a decrease in their relative abundance after infection. The endophytic fungal community was characterized by 3 phyla and 10 genera. After infection, the relative abundance of 2 phyla (Anthophyta and Basidiomycota) and 7 genera (Eucalyptus, Candida, Kluyveromyces, Talaromyces, Oidiodendron, Nigrospora, and Pestalotiopsis) decreased, whereas the relative abundance of the Colletotrichum genus increased dramatically. The LEfSe (Linear discriminant analysis Effect Size) analysis indicated that significant biomarkers were more prevalent in endophytic bacteria than in endophytic fungi in the avocados. In endophytic bacteria, the key biomarkers included the Firmicutes phylum (Bacilli class), Proteobacteria phylum (Gammaproteobacteria class, Pseudomonadales order, Pseudomonadaceae family, and Pseudomonas genus), Flavobacteriales order, Weeksellaceae family, and Chryseobacterium genus. In endophytic fungi, the important biomarkers were Saccharomycetes class (Saccharomycetales order), Glomerellales order (Glomerellaceae family and Colletotrichum genus), and Botryosphaeriales order (Botryosphaeriaceae family and Lasiodiplodia genus). These results may provide a theoretical basis for the development of future biological agents for avocado anthracnose.